Impact of angiotensin-converting enzyme inhibition on platelet tissue factor expression in stroke-prone rats. Issue 6 (June 2018) - Brambilla, Marta; Gelosa, Paolo; Rossetti, Laura; Castiglioni, Laura; Zara, Chiara; Canzano, Paola; Tremoli, Elena; Sironi, Luigi; Camera, Marina
Abstract : Objective: Hypertension is a well known risk factor for thrombotic events such as myocardial infarction and stroke. Platelets express tissue factor (TF), the key activator of blood coagulation and thrombus formation. The number of TF-positive platelets increases in pathological conditions characterized by thrombotic complications but whether this occurs in hypertension is unknown. Here we investigated whether platelet TF expression is increased in a hypertensive status through a mechanism acting on megakaryocytes; the phenomenon could be modulated by antihypertensive drug as captopril; angiotensin (AngII) influences platelet TF expression. Methods: Spontaneously hypertensive stroke prone (SHRSP) rats received standard diet (StD) or a Japanese high-salt permissive diet (JpD). After 3 weeks, JpD animals were randomized to receive captopril or vehicle. Normotensive Wistar Kyoto (WKY) rats were used as controls. Cell-associated TF expression and activity were analyzed by flow cytometry and calibrated automated thrombogram, respectively. Results: Hypertensive StD-SHRSP showed an increased number of TF-positive platelets compared with normotensive WKY. After JpD administration, SHRSP developed severe hypertension and renal damage; the number of TF-positive megakaryocytes significantly increased compared with StD-SHRSP resulting in a higher number of TF-positive platelets with a faster kinetic of thrombin generation. These effects were reverted by captopril. Ex-vivo stimulation of platelets, isolated from normotensive WKY and from healthy individuals, with AngII induced a concentration-dependent increase of surface-associated TF expression. Conclusion: The current study shows for the first time that in hypertension the number of TF-positive megakaryocytes increases thus releasing in the circulation more platelets carrying a functionally active TF. AngII stimulates platelets to express TF. Abstract : Supplemental Digital Content is available in the text